Subfertility in young male mice mutant for chromatin remodeller CECR2. Issue 2 (21st January 2022) - Norton, Kacie A; Humphreys, Ross; Weatherill, Chelsey; Duong, Kevin; Nguyen, Vivian V; Kommadath, Arun; Niri, Farshad; Stothard, Paul; McDermid, Heather E
Abstract : Defects in spermatogenesis are an important cause of male infertility. Multiple aspects of spermatogenesis are controlled by chromatin remodellers, including regulating transcription. We previously described mutations in chromatin remodelling gene Cecr2 that resulted in the lethal neural tube defect exencephaly in most mutant mice and subfertility in mice that were non-penetrant for exencephaly. Here, we show that the severity of male subfertility is dependent on age. Cecr2 GT/Del males contain two mutant alleles, one of which is hypomorphic and therefore produces a small amount of protein. These males sire the fewest pups just after sexual maturity (88% fewer than Cecr2 +/+ at P42–60) but improve with age (49% fewer than Cecr2 +/+ at P81–100), although never completely recovering to Cecr2 +/+ (wild type) levels. When young, they also have defects in testis histology, in vivo fertilization frequency, sperm number and motility, and testis weight that show similar improvement with age. Immunostaining of staged seminiferous tubules showed CECR2 in type A, intermediate and B spermatogonia, and less in preleptotene and leptotene spermatocytes. Histological defects were first apparent in Cecr2 GT/Del testes at P24, and RNA-seq analysis revealed 387 differentially expressed genes. This included 66 genes on the X chromosome (almost double the number on any other chromosome), all more highly expressed in Cecr2 GT/Del testes. This inappropriate expression of X chromosome genes could be caused by a failure of effective meiotic sex chromosome inactivation. We identify several abnormally expressed genes that may contribute to defects in spermatogenesis at P24. Our results support a role for Cecr2 in juvenile spermatogenesis.